2012
DOI: 10.1016/j.mcn.2011.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+-independent syntaxin binding to the C2B effector region of synaptotagmin

Abstract: Although synaptotagmin I, which is a calcium (Ca(2+))-binding synaptic vesicle protein, may trigger soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE)-mediated synaptic vesicle exocytosis, the mechanisms underlying the interaction between these proteins remain controversial, especially with respect to the identity of the protein(s) in the SNARE complex that bind(s) to synaptotagmin and whether Ca(2+) is required for their highly effective binding. To address these questions, native p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 58 publications
(77 reference statements)
1
5
0
Order By: Relevance
“…The effect of the Syt1 R322E, K325E mutant ( Fig. 4 ) as well as reported observations 29 , 30 , 35 , 44 , 45 suggests a functional role for the polybasic region.…”
Section: Model Of Syt1 Mediated Ca 2+ Triggeringsupporting
confidence: 88%
“…The effect of the Syt1 R322E, K325E mutant ( Fig. 4 ) as well as reported observations 29 , 30 , 35 , 44 , 45 suggests a functional role for the polybasic region.…”
Section: Model Of Syt1 Mediated Ca 2+ Triggeringsupporting
confidence: 88%
“…There are several C2 domains that directly interact with SNARE proteins (32-36, 46, 47) with differing specificity. The C2 domains of rabphilin and Rab3-interacting molecule bind only to SNAP-25 (34,35,46), and the C2 domains of synaptotagmin, DOC2, and otoferlin bind to both SNAP-25 and syntaxins, although the Ca 2ϩ dependence and preference for distinct syntaxin isoforms vary (32,33,36,47). PRIP-C2 interacted with both syntaxin 1 and SNAP-25, but the C2 domain of PLC-␦1, despite its structural similarity, did not bind to either syntaxin 1 or SNAP-25.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these Ca 2+ -binding loops, the C2B domain contains a polybasic region (KKKK, 324-327; Fig. 1) that is close to Ca 2+ -binding loops and is enriched with lysine residues [23] that interact with anionic phospholipids [26][27][28][29][30][31][32] or the SNARE complex [33][34][35][36][37][38][39][40][41][42][43][44]. Evidence in 1992 showed that Syt1 interacts with anionic membrane [19] or with SNARE proteins [39] by electrostatic interaction.…”
Section: Syt1 As a Ca 2+ Sensor For Fast Exocytosismentioning
confidence: 99%
“…Many groups have demonstrated Syt1 interaction with SNARE proteins [33][34][35][36][37][38][39][40][41][42][43][44]. The polybasic region in the C2B domain of Syt1 (KKKK, 324-327; Fig.…”
Section: Molecular Mechanisms Of Syt1 To Trigger Fusionmentioning
confidence: 99%
See 1 more Smart Citation